2020
DOI: 10.3390/ijerph17113775
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Kidney Injury among Construction Workers Exposed to Heat Stress: A Longitudinal Study from Saudi Arabia

Abstract: Saudi Arabia (SA) is one of the hottest countries in the world. This study was conducted to assess the impact of summer heat stress in Southeastern SA on short-term kidney injury (KI) among building construction workers and to identify relevant risk factors. Measurements of urinary albumin-creatinine ratio (ACR), height, weight, hydration, symptoms, daily work and behavioral factors were collected in June and September of 2016 from a cohort of construction workers (n = 65) in Al-Ahsa Province, SA. KI was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 86 publications
0
26
0
1
Order By: Relevance
“…These workers tend to have sleep deprivation that leads to increasing daytime sleepiness during working hours and shift work schedule [ 8 , 9 , 10 ]. Several previous studies have reported that construction workers were likely to experience fatigue, pain, and specific diseases due to sleep disturbances [ 10 , 11 , 12 , 13 ]. Consequently, there is ongoing research to identify the relationship among sleep disturbances, occupational environment for shift workers, and health problems in diverse groups of workers [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These workers tend to have sleep deprivation that leads to increasing daytime sleepiness during working hours and shift work schedule [ 8 , 9 , 10 ]. Several previous studies have reported that construction workers were likely to experience fatigue, pain, and specific diseases due to sleep disturbances [ 10 , 11 , 12 , 13 ]. Consequently, there is ongoing research to identify the relationship among sleep disturbances, occupational environment for shift workers, and health problems in diverse groups of workers [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, we were surprised by the lack of studies on construction workers given the physical demands and the long exposures to thermal radiation. This population warrants further investigation given that construction workers account for 36% of all heat-related deaths in the United States (76) and that albuminuria associated with construction work has been reported in other countries (77). Second, despite the US OSHA recognizing that mail/package delivery workers are exposed to occupational heat stress, our literature search did not reveal any studies in this population.…”
Section: Discussionmentioning
confidence: 80%
“…18 A longitudinal study among Indian construction workers in Saudi Arabia suggested that exposure to heat stress, long working hours, dehydration, sleep deprivation, and obesity may induce the risk to kidney health in workers. 19 In Ponorogo district of Indonesia, 18% of the patients with chronic renal failure were former migrant workers. 20 A qualitative study among Indonesian migrant workers with CKD reported that they were also involved in unhealthy eating, such as a high intake of alcohol and soft drinks and high consumption of fast food.…”
Section: Discussionmentioning
confidence: 99%